Effect of Adding Flue Gas Desulphurization Gypsum on the Transformation and Fate of Nitrogen during Composting. Issue 4 (1st October 2016) - Guo, Xiaobo; Lu, Yanyu; Li, Qunliang
ABSTRACT: The objective of this study was to investigate the effect of adding flue gas desulphurization gypsum (FGDG) on the transformation and fate of nitrogen during co-composting of dairy manure and pressmud of a sugar refinery. The ammonia absorption of FGDG was investigated. The changes in compost temperature, pH, electrical conductivity (EC), moisture, organic matter, the C/N ratio, Kjeldahl N, NH4 + -N, NO2 − -N, NO3 − -N were assessed. The addition of FGDG did not significantly affect compost temperature, pH, EC, moisture, and organic matter degradation. However, the addition of FGDG significantly increased the NH4 + -N content in the compost during the thermophilic phase, and the NH4 + -N maximal content in the compost with FGDG (CP+G) was 59.9% more than that in the compost without FGDG (CP–G). FGDG was thought to create the formation of (NH4 )2 SO4 and the cation exchange between NH4 + and Ca 2+ . The NO2 − -N content in the CP+G peaked on day 15, and was not observed in the CP–G. In the final compost products, the NO3 − -N concentration in the CP–G was more than that in the CP+G, which was 1451 (CP–G) and 1109 mg· kg −1 (CP+G) dry material. This might be due to the NO2 − accumulation in the CP+G, which accelerated N loss in the form of N2 O. There is a strong correlation between N2 O emission and NO2 − -N accumulation in the composting process. Compared with the original N content in the compost mixture, the N loss in CP–G and CP+G were 15.0 and 10.8%, respectively. These results revealed that NH4 + -N conservation effect was improved during the thermophilic phase and the total N loss was mitigated by adding FGDG into composting materials. FGDG could be utilized as a potential amendment to conserve nitrogen during composting.